2011
DOI: 10.1136/gutjnl-2011-300535
|View full text |Cite
|
Sign up to set email alerts
|

Interval cancers in a FOBT-based colorectal cancer population screening programme: implications for stage, gender and tumour site

Abstract: Although GFOBT screening is associated with substantial interval cancer rates that increase with screening round, the absolute numbers do not. Interval cancers are associated with a better prognosis than cancers arising in a non-screened population, and GFOBT appears to preferentially detect cancers in men and the left side of the colon at the expense of cancers in women and in the right colon and rectum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
128
7
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(169 citation statements)
references
References 26 publications
31
128
7
3
Order By: Relevance
“…Since then, recent findings at two academic endoscopy units in North America have indicated that the prevalence of proximal colon serrated lesions in patients undergoing screening colonoscopy in a clinical setting may be higher than previously reported [63] and a significant proportion of proximal serrated lesions may be missed during colonoscopy [64]. Interval cancers have also been associated with proximal location in a population-based screening setting in Europe [65]. These findings also illustrate the importance of the recommendations in the guidelines for routine documentation of the morphology and topography of lesions detected in CRC screening [19,21].…”
Section: Author Manuscriptmentioning
confidence: 95%
“…Since then, recent findings at two academic endoscopy units in North America have indicated that the prevalence of proximal colon serrated lesions in patients undergoing screening colonoscopy in a clinical setting may be higher than previously reported [63] and a significant proportion of proximal serrated lesions may be missed during colonoscopy [64]. Interval cancers have also been associated with proximal location in a population-based screening setting in Europe [65]. These findings also illustrate the importance of the recommendations in the guidelines for routine documentation of the morphology and topography of lesions detected in CRC screening [19,21].…”
Section: Author Manuscriptmentioning
confidence: 95%
“…This raises some concern as it has been found that more women have interval cancers than men in Scotland. 15 Because this is the fourth screening round in NHS Tayside, and most who participate in screening do so regularly 16 , this implies that the current screening strategy misses significant neoplasia and it might be that evolution to an approach that uses an automated quantitative FIT would be of advantage in this regard. 11 Men did, however, have more adenomas of all types than did women.…”
Section: Discussionmentioning
confidence: 99%
“…There are few publications on interval cancers but a recent study showed that, of the cancers diagnosed in the screened population, interval cancers comprised 31.2% in the first round, 47.7% in the second and 58.9% in the third: the number of interval cancers increased slightly over screening rounds and, as expected, there was a concomitant decline in the numbers of screen-detected cancers. 47 Thus, gFOBT screening was associated with substantial interval cancer rates that increased with screening round and appears to preferentially detect cancers in men and the left side of the colon at the expense of cancers in women and in the right colon and rectum. Interval cancers are thus commoner in women and it may be that women are considerably disadvantaged by the use of currently available gFOBT.…”
Section: Fraser Faecal Haemoglobin Measurementsmentioning
confidence: 99%
“…50 A number of possible explanations for the gender difference have been postulated. 46,47 Men have higher blood haemoglobin concentrations than women in their reproductive years of life but most women who are screened are probably postmenopausal when such differences are less. It might be that men take more medicines that inhibit clotting or cause gastrointestinal tract bleeding than women.…”
Section: Fraser Faecal Haemoglobin Measurementsmentioning
confidence: 99%